Representasi Kenakalan Remaja Dalam Film Crow Zero - Candra saputra; Aliasan Aliasan; Muslimin Muslimin (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Representation of Juvenile Delinquency in the Film Crow Zero". The aim of this research is to find out the meaning of denotation, connotation and myth in the film "Crow Zero", and to find out the representation contained in the film "Crow Zero". The type of research used is descriptive research with a qualitative approach. The data collection techniques used are primary data and secondary data. The object of this research is the film "Crow Zero" and the technique used is Roland Barthes' semiotic technique. The results of this research are the meaning of denotation, connotation and myth in the film "Crow Zero". Denotation is the first stage which uses Roland Barthes' semiotic method, connotation is the original nature of the sign, and myth is a second level system of meaning. The message contained in the film "Crow Zero" is that by uniting you can achieve a certain goal even though the method chosen, namely violence, is an inappropriate method.